Exploring Entrepreneurial Leadership: A Case Study On Small Medium Entreprise’s Owner In Jakarta - Safitri, Nurul; Sakapurnama, Eko (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2018)
Leadership style becomes the important things a crucial factor to ensure the success of how the SME’s small business owners in managing their business operation successfully. This study aims to analyzing the leadership style of the Small and Medium-sized Enterprise’s owner whom located in Jakarta. By using the Leader Behavior Description Questionnaire (LBDQ), this empirical study will analyzes whether the entrepreneur has acquire initiating structure or consideration while governed its business. The research method issues mixed method, both quantitative using survey through purposive sampling toward 30 entrepreneurs that located in Jakarta, and qualitative ones method using is applied through in-depth interview toward on several key informants. The result is shows behavioral pattern of the entrepreneurs have is high initiating structure which means they focus on the production and slightly high consideration that described that they also maintain its their staff as a member of the big family at their business.